A survey of Himalayan rangeland weeds in Tinjure-Milke-Jaljale area, eastern Nepal - Limbu, Dil Kumar; Koirala, Madan; Shang, Zhanhuan (Nepalese Journal of Biosciences, 2013)
Eight common rangeland weeds including Anaphalis contorta, Berberis erythroclada, Euphorbia wallichii, Potentilla lineate, Prunella vulgaris, Pteris aspericaulis, Senecio chrysanthemoides and Swertia pedicellata were recorded from the rangelands of Tinjure-Milke-Jaljale area in the present study, among which Senecio chrysanthemoides and Swertia pedicellata were the most obnoxious species responsible for the habitat degradation for wildlife, reduction in biodiversity, curtailment of forage resources and alternation of ecosystem and functions. The main reason for rapid weed invasion was the lack of awareness of the gravity of situation among the stakeholders hindering adoption of effective weed control measures. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7486 Nepalese Journal of Biosciences 2 : 24-30 (2012)